Activation of Sterol Regulatory Element Binding Factors by Fenofibrate and Gemfibrozil Stimulate Myelination in Zebrafish - Yuhei Nishimura; Yoshifumi Ashikawa; Shiko Okabe; Shota Sasagawa; Soichiro Murakami; Mizuki Yuge; Koki Kawaguchi; Reiko Kawase; TOSHIO TANAKA (Frontiers Media S.A., 2016)
Oligodendrocytes are major myelin-producing cells and play essential roles in the function of a healthy nervous system. However, they are also one of the most vulnerable neural cell types in the central nervous system (CNS), and myelin abnormalities in the CNS are found in a wide variety of neurological disorders, including multiple sclerosis, adrenoleukodystrophy, and schizophrenia. There is an urgent need to identify small molecular weight compounds that can stimulate myelination. In this study, we performed comparative transcriptome analysis to identify pharmacodynamic effects common to miconazole and clobetasol, which have been shown to stimulate myelination by mouse oligodendrocyte progenitor cells (OPCs). Of the genes differentially expressed in both miconazole- and clobetasol-treated mouse OPCs compared with untreated cells, we identified differentially expressed genes (DEGs) common to both drug treatments. Gene ontology analysis revealed that these DEGs are significantly associated with the sterol biosynthetic pathway, and further bioinformatics analysis suggested that sterol regulatory element binding factors (SREBFs) might be key upstream regulators of the DEGs. In silico screening of a public database for chemicals associated with SREBF activation identified fenofibrate, a peroxisome proliferator-activated receptor α (PPARα) agonist, as a drug that increases the expression of known SREBF targets, raising the possibility that fenofibrate may also stimulate myelination. To test this, we performed in vivo imaging of zebrafish expressing a fluorescent reporter protein under the control of the myelin basic protein (mbp) promoter. Treatment of zebrafish with fenofibrate significantly increased expression of the fluorescent reporter compared with untreated zebrafish. This increase was attenuated by co-treatment with fatostatin, a specific inhibitor of SREBFs, confirming that the fenofibrate effect was mediated via SREBFs. Furthermore, incubation of zebrafish with another PPARα agonist, gemfibrozil, also increased expression of the mbp promoter-driven fluorescent reporter in an SREBF-dependent manner. These results suggest that activation of SREBFs by small molecular weight compounds may be a feasible therapeutic approach to stimulate myelination.